A non-alcoholic Wernicke's encephalopathy case with atypical MRI findings: Clinic versus radiology. Issue 5 (October 2015) - Guler, Ayse; Alpaydin, Sezin; Sirin, Hadiye; Calli, Cem; Celebisoy, Neşe
Wernicke's Encephalopathy is an acute neuropsychiatric syndrome that can be seen in both alcohol abusers and non-alcoholic population as a result of thiamine deficiency. We herein report a non-alcoholic patient with typical clinical presentations but atypical MRI findings. Early clinical suspicion of WE is especially important in non-alcoholic patients with atypical MRI findings. The diagnosis of this group is more difficult to make and the prognosis of the syndrome mostly depends on early initiation of thiamine supplementation.